2010
DOI: 10.1037/a0021121
|View full text |Cite
|
Sign up to set email alerts
|

Psychologists' competence to treat lesbian, gay and bisexual clients: State of the field and strategies for improvement.

Abstract: Recognizing research which suggests that many practicing psychologists enter the field without training or with inadequate training in the knowledge, skills, and awareness needed to treat lesbian, gay, and bisexual (LGB) clients, the authors in this Focus on Ethics provide suggestions for psychologists seeking competence with this population. In the lead article, Lyons fleshes out the contours of competent practice, presents the current state of psychologist competence, and calls for greater levels of competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Incompetence and poor training were identified as responsible for inferior psychological treatment offered to lesbian, gay, and bisexual clients whose overall treatment dissatisfaction was high, and even higher for those from minority race/ethnicity categories (Lyons, Bieschke, Dendy, Worthington, & Georgemiller, 2010). Higher levels of stress and psychopathologies, as well as specialized treatment recommendations, were noted in minority individuals self-identified as LGBTQ (Chae & Ayala, 2010), in AsianAmericans who were LGBTQ (Szymanski & Sung, 2010) and in American Indian and Alaska Native women self-identified as bisexual, lesbian or "two spirit" (Lehavot, Walters, & Simoni, 2009).…”
Section: Tentative Implications For Social Work Educationmentioning
confidence: 96%
“…Incompetence and poor training were identified as responsible for inferior psychological treatment offered to lesbian, gay, and bisexual clients whose overall treatment dissatisfaction was high, and even higher for those from minority race/ethnicity categories (Lyons, Bieschke, Dendy, Worthington, & Georgemiller, 2010). Higher levels of stress and psychopathologies, as well as specialized treatment recommendations, were noted in minority individuals self-identified as LGBTQ (Chae & Ayala, 2010), in AsianAmericans who were LGBTQ (Szymanski & Sung, 2010) and in American Indian and Alaska Native women self-identified as bisexual, lesbian or "two spirit" (Lehavot, Walters, & Simoni, 2009).…”
Section: Tentative Implications For Social Work Educationmentioning
confidence: 96%
“…First, it is suggested that college counselors would be professionally wise, and perhaps ethically obliged, to seek training and experience in working with members of sexual minority groups. A considerable body of literature is developing on counseling and psychotherapy with individuals who are sexual minorities (Lyons, Bieschke, Dendy, Worthington, & Georgemiller, 2010); given that it is likely that somewhere between 8% and 19% of counseling center clients identify as a sexual minority, competence with this portion of clients is essential. In addition, the results imply that further outreach for college students who identify as sexual minorities may be necessary, especially among those who seem to endorse distress but may not seek counseling as commonly as other groups (e.g., bisexual and questioning students).…”
Section: Implications For Practicementioning
confidence: 99%
“…This may assist clinicians in developing interventions within the integrated care setting to most effectively address the needs of LGB women and men who seek mental health services (Lyons, Bieschke, Dendy, Worthington, & Georgemiller, 2010). …”
mentioning
confidence: 99%